High-density genotyping study identifies four new susceptibility loci for atopic dermatitis. - Irvine, Alan; McAleer, Maeve (My University, 2013)
Atopic dermatitis is a common inflammatory skin disease with a strong heritable component. Pathogenetic models consider keratinocyte differentiation defects and immune alterations as scaffolds, and recent data indicate a role for autoreactivity in at least a subgroup of patients. FLG (encoding filaggrin) has been identified as a major locus causing skin barrier deficiency. To better define risk variants and identify additional susceptibility loci, we densely genotyped 2,425 German individuals with atopic dermatitis (cases) and 5,449 controls using the Immunochip array followed by replication in 7,196 cases and 15,480 controls from Germany, Ireland, Japan and China. We identified four new susceptibility loci for atopic dermatitis and replicated previous associations. This brings the number of atopic dermatitis risk loci reported in individuals of European ancestry to 11. We estimate that these susceptibility loci together account for 14.4% of the heritability for atopic dermatitis.
PUBLISHED
Keywords: Atopic dermatitis; Immunology, Inflammation & Infection